2022
DOI: 10.1093/cvr/cvac151
|View full text |Cite
|
Sign up to set email alerts
|

Multi-species meta-analysis identifies transcriptional signatures associated with cardiac endothelial responses in the ischaemic heart

Abstract: Aim Myocardial infarction remains the leading cause of heart failure. The adult human heart lacks the capacity to undergo endogenous regeneration. New blood vessel growth is integral to regenerative medicine necessitating a comprehensive understanding of the pathways that regulate vascular regeneration. We sought to define the transcriptomic dynamics of coronary endothelial cells following ischaemic injuries in the developing and adult mouse and human heart and to identify new mechanistic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“… 52 Li et al also found significantly elevated ZFP36 protein levels in ischemic human heart tissue and knockdown of ZFP36 in HCMECs using siRNA significantly inhibited cell proliferation. 53 Our analysis suggests that ZFP36 may be one of the targets of endothelial cell injury by NETs during MI and may be a promising novel target for the treatment of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 84%
“… 52 Li et al also found significantly elevated ZFP36 protein levels in ischemic human heart tissue and knockdown of ZFP36 in HCMECs using siRNA significantly inhibited cell proliferation. 53 Our analysis suggests that ZFP36 may be one of the targets of endothelial cell injury by NETs during MI and may be a promising novel target for the treatment of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 84%
“…The VEGFB-iECs were not affected during pregnancy, and they were only increased by 4.3% in WT mice subjected to LAD ligation. Interestingly, recent analyses of transcriptomic changes in ischemic human hearts and in mice after MI [64][65][66][67] do not indicate significant upregulation of VEGFB-iEC marker transcripts. Thus, the unique ability of VEGF-B to expand the VEGFB-iEC population likely underlies the protective effects of VEGF-B in the ischemic heart.…”
Section: Discussionmentioning
confidence: 93%
“…Zhang et al reported that enhanced expression of ZFP36 in aortic endothelial cells might reduce vascular inflammation through direct binding to target cytokine mRNAs 36 . A meta-analysis of single-cell RNA sequencing targeting multiple species revealed that ZFP36 regulates human coronary artery endothelial cell proliferation in ischemic hearts and determined that VEGF-C administration in vivo enhances clonal expansion of the cardiac vascular after myocardial infarction 37 . Our research indicates that CDKN1A, SAT1, and ZFP36 share overlapping upstream transcription factors, which are in fact members of the AP-1 family, playing an important role in regulating cellular proliferation, differentiation, and biological response processes 38 .…”
Section: Discussionmentioning
confidence: 99%